Choosing caesareans? The perceptions and experiences of childbirth among mothers from higher socio-economic households in Dhaka. Issue 11 (2nd November 2018) - Akhter, Sanzida; Schech, Susanne
Abstract: In this paper, we examine the perceptions and experiences of childbirth among a group of wealthier women in Dhaka through in-depth interviews. We find that a number of factors including preference for Caesarean Section (CS), socio-economic position, family structure, and perceptions of modern childbirth contributed to the women's overuse of medical childbirth services. Furthermore, women's capacity to purchase modern maternal health care in the private sector did not necessarily ensure high quality care in a health system which approaches maternal healthcare as a profit-making enterprise rather than as an essential human right.